Adaptação de uma impressora 3D de extrusão de pasta polimérica para extrusão de pasta cerâmica - Segala, Luigi Roehrig (2023)
Additive manufacturing (AM) is a process that involves adding material in successive layers, thus creating a three-dimensional object. The most commonly used materials with this technology are polymers, but the process can also be adapted for the use of others, such as metals and pre-ceramic materials. This work will address the stages of developing an extrusion head to adapt a 3D printer to produce parts from ceramic pastes. The project became necessary due to specific demands within the university laboratory to enable the continuation of research. In this context, the solution found was to develop an extrusion head using a syringe that could be attached to an existing 3D printer originally intended for the extrusion of plastic parts. Due to the characteristics of the materials and the process, design and operating mechanism changes were necessary to achieve controlled extrusion. Through these efforts, it was possible to successfully adapt the 3D printer for the production of ceramic parts. The developed extrusion head proved efficient in handling ceramic pastes, allowing for the continuity of research in the university laboratory. This adaptation has opened up new possibilities for 3D printing of various materials, expanding the applications and potential of this technology in the field of manufacturing.